Improving Student Learning Motivation in Islamic Education Learning Using an Activity-Based Approach at SD Negeri Inpres Baralau - Ernawati, Sri (MANDAILING GLOBAL EDUKASIA, 2025)
This study investigates the effectiveness of an activity-based approach in enhancing students' learning motivation in Islamic Education at SD Negeri Inpres Baralau. Learning motivation is a critical factor that significantly influences students’ academic success, particularly in religious education where engagement can be challenging due to traditional and passive instructional methods. The research employed a classroom action research design conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. Data were collected through observation sheets, student questionnaires, and teacher interviews to triangulate findings. The participants involved were 32 students in Grade V during the 2024/2025 academic year. The findings revealed a marked improvement in students’ motivation following the implementation of activity-based learning strategies, including group discussions, role-playing, games, and creative project assignments related to Islamic values. Quantitative data showed a significant increase in students’ motivation scores, rising from an average of 62.3 in the pre-cycle to 76.8 in the first cycle and 85.4 in the second cycle. Qualitative observations supported these results, indicating higher levels of enthusiasm, participation, and sustained attention during lessons. This research highlights that integrating interactive and student-centered learning activities into Islamic Education can foster a more engaging and motivating learning environment. The study recommends adopting activity-based approaches in primary religious education to cultivate not only students’ interest but also a deeper understanding and internalization of Islamic values. These findings are relevant for educators, policymakers, and curriculum developers aiming to improve educational practices in faith-based learning contexts. Future research may explore the long-term impact of such approaches across different educational levels and cultural settings.